A CRITICAL ANALYSIS OF SOUMANASYAM GARBHADHARANANAM SHRESTAM - Bharathi, *K; Pushpalatha, B; sharma, Sushila (International Journal of Ayurveda and Pharma Research, 2016)
World Health Organization defines the health as a State of physical, psychological, social and spiritual wellbeing, not merely the absence of disease, the same thought of holistic approach of health conceived some centuries ago by the oriental intellectuals especially Ayurvedic classics with the beautiful definition : Samadosha samagnicha samadhatu malakriya, Prasannathmendriya mana: swasthaithiabhidheeyateâ€ which shows the in depth foresight towards physiological as well as psychological state in maintaining the positive health. The mental equilibrium is also needed for conception (Garbhavakranti), development of the foetus (Garbhavridhi).The present paper attempts to analyze and establish the role of Mano samyata in Garbhavakranti (conception), Garbhinicharya (antenatal care) and Garbhavridhi (fetal development) through the immune â€“Nervous â€“Endocrine orchestra.